1994
DOI: 10.1128/aac.38.6.1320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexamethasone on therapy of experimental penicillin- and cephalosporin-resistant pneumococcal meningitis

Abstract: Treatment of pneumococcal meningitis has become problematic because of the emergence of penicillin-and cephalosporin-resistant strains and because of the concern that dexamethasone therapy might reduce penetration of antibiotics into the cerebrospinal fluid (CSF). We addressed these issues with our rabbit meningitis model by studying two pneumococcal isolates that were resistant to penicillin and ceftriaxone and susceptible to vancomycin and rifampin. Ceftriaxone, vancomycin, and rifampin were given alone or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
4
4

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(112 citation statements)
references
References 35 publications
(45 reference statements)
7
97
4
4
Order By: Relevance
“…For patients with inflamed meninges, bactericidal CSF concentrations of vancomycin against susceptible pathogens are reached during high intravenous doses (2). Adjunctive dexamethasone therapy as recommended for community-acquired bacterial meningitis in patients reduced CSF vancomycin concentrations substantially, resulting in a delay in CSF sterilization in a rabbit model of experimental meningitis (188). Based on these data, those authors concluded that when dexamethasone is used as an adjunctive therapy for bacterial meningitis in areas with high rates of occurrence of penicillinresistant pneumococci, the combination of rifampin and ceftriaxone should be preferred instead of vancomycin and ceftriaxone (188) (see below).…”
Section: Glycopeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with inflamed meninges, bactericidal CSF concentrations of vancomycin against susceptible pathogens are reached during high intravenous doses (2). Adjunctive dexamethasone therapy as recommended for community-acquired bacterial meningitis in patients reduced CSF vancomycin concentrations substantially, resulting in a delay in CSF sterilization in a rabbit model of experimental meningitis (188). Based on these data, those authors concluded that when dexamethasone is used as an adjunctive therapy for bacterial meningitis in areas with high rates of occurrence of penicillinresistant pneumococci, the combination of rifampin and ceftriaxone should be preferred instead of vancomycin and ceftriaxone (188) (see below).…”
Section: Glycopeptidesmentioning
confidence: 99%
“…When rifampin was used with ceftriaxone for the treatment of experimental meningitis caused by penicillin-resistant S. pneumoniae in rabbits, bacteriologic cure occurred promptly, with or without dexamethasone therapy (188). Although clinical data on the efficacy of rifampin in patients with S. pneumoniae meningitis are scarce, some authors recommended that in areas with high rates of occurrence of penicillin-resistant pneumococcal strains, the combination of ceftriaxone plus rifampin instead of vancomycin should be preferred, or rifampin, vancomycin, and ceftriaxone should be administered together when adjunctive dexamethasone is used (188,243).…”
Section: Rifamycinsmentioning
confidence: 99%
“…The effect of dexamethasone therapy on the activity of the cephalosporins and vancomycin and their penetration into the CSF of these patients is required before definitive recommendations can be made. Data derived from studies of experimental pneumococcal meningitis clearly indicate that dexamethasone reduces the CSF penetration of ceftriaxone and vanco-mycin sufficiently to alter the clearance of resistant organisms from CSF cultures [30]. Penetration of rifampin into the CSF appears to be unaffected by concomitant dexamethasone therapy.…”
Section: Commentmentioning
confidence: 98%
“…In the rabbit model, vancomycin levels in CSF were reduced in the presence of dexamethasone and this was associated with a delay in CSF sterilization of penicillin-susceptible or penicillin-and cephalosporin-resistant isolates. 39,40 Relatively little is known about the pharmacology of vancomycin entrance into CSF in patients also receiving dexamethasone. In one study from Spain, 11 adults received vancomycin along with dexamethasone (0.25 mg/kg q 6 hours x 4 days) for pneumococcal meningitis.…”
Section: Clinical Trialsmentioning
confidence: 99%